Liberal acceptance bias, momentary aberrant salience, and psychosis: an experimental experience sampling study - Reininghaus, Ulrich (Schizophrenia bulletin, 2019)
Abstract. Cognitive models of psychosis posit that reasoning biases are an important mechanism contributing to the formation of psychotic symptoms, in part thr